2002
DOI: 10.1002/ca.1085
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of connections between the musculocutaneous and median nerves in the axilla and arm

Abstract: Variations in connections between the musculocutaneous and median nerves in the arm are not as uncommon as was once thought. This opinion led us to perform a study in 138 cadavers (66 male, 72 female). These variations were seen in 64 cadavers (46.4%), 9 bilaterally and 55 unilaterally (26 right and 29 left); in total, therefore, variations were observed in 73 out of 276 arms (26.4%), 42 male and 31 female. No statistically significant differences by gender and side were observed. We classify the variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
135
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 18 publications
13
135
0
6
Order By: Relevance
“…4,10 In the present case only one communication is seen, which is a rare case finding. Le Minor 2 has classified the variations of MCN and MN into five types.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…4,10 In the present case only one communication is seen, which is a rare case finding. Le Minor 2 has classified the variations of MCN and MN into five types.…”
Section: Discussionmentioning
confidence: 46%
“…In a recent study by Choi et al, communications between MCN and MN have been broadly classified into three types. 4 In type I: the MCN and MN were fused; in type II: there was one connecting branch between the MCN and MN and in type III: two connecting branches were present between MCN and MN. So, the present case coincides with type II category of Choi D classification.…”
Section: Discussionmentioning
confidence: 99%
“…Pattern of motor branching of this nerve in human fetuses were also studied by Kervancioglu et al (2011). Communication between musculocutaneous and median nerves in arm has been observed in 46.4% studied cases by Choi et al (2002). Frequency of this anomaly has been reported 63% by Loukas & Aqueelah (2005).…”
Section: Discussionmentioning
confidence: 97%
“…4 Aktan et al (2001) in their study of 48 limbs, have reported median nerve communications with musculocutaneous nerve in 5 (5%) limbs. 24 Choi et al (2002) in their study of 276 upper limbs found median nerve communications with musculocutaneous nerve in 73 (26.4%) limbs. In 9 cadavers these were bilateral.…”
Section: Muscles Of Anterior Compartment Of Arm Innervated By Median mentioning
confidence: 91%
“…In 9 cadavers these were bilateral. 25 Beheiry (2004) in his study of 60 cadaver arms noticed communications between median nerve and musculocutaneous nerve in 3 (5%) limbs. 17 Guttenberg and Ingolotti (2009) in their study of 56 upper limbs have reported median nerve communications with musculocutaneous nerve in 30 (53.6%) limbs.…”
Section: Muscles Of Anterior Compartment Of Arm Innervated By Median mentioning
confidence: 99%